50 kGy of gamma irradiation does not affect the leachability of mineral soils and sediments. Issue 1 (30th October 2014) - Gore, Damian B.; Snape, Ian
<x content-type="archive" xml:space="preserve">Abstract</x> Sterilization of soils and sediments can release them from quarantine restrictions. Gamma irradiation is effective at sterilization but can damage materials and in so doing affect their suitability for environmental research. Duplicate samples of a wide range of mineral soils and sediments were subject to an acetic acid extraction before and after 50 kGy gamma irradiation. This amount of gamma irradiation did not affect the leachability of a range of analytes from the soils and sediments.